Heating of Low and High Temperature PEM Fuel Cells with Alternating Current1. Issue 3 (5th June 2018) - Kurz, T.; Küfner, F.; Gerteisen, D.
Abstract: An innovative method for heating proton exchange membrane fuel cell (PEMFC) stacks during start‐up by direct heating of the cells is presented and investigated. By imposing an alternating current on the stack, heat is generated locally depending on the internal cell resistance. It is shown, that an alternating current (AC) perturbation with a suitable high frequency mainly heats the ohmic resistors which are membrane and contact interfaces. The electrodes are protected from voltage cycling, due to (de)charging currents of the double layer capacitances at high frequency. This AC heating technique is applied on a 6‐cell low temperature (LT) PEMFC stack and a 30‐cell high temperature (HT) PEMFC stack, both with an active area of approximately 30 cm 2 . Both stacks are heated under realistic temperature conditions, the LTPEMFC stack from sub‐zero temperatures to 40 °C and the HTPEMFC stack from room temperature to 120 °C. Heating times are shown and discussed for different stack geometries and voltages. In both cases, this strategy leads to a short and efficient heating, as the cells are heated directly and not externally by coolant or other stack components.